Worldly reasons: an ontological inquiry into motivating considerations and normative reasons - Mantel, Susanne (Pacific philosophical quarterly, 2017)
In this article I advocate a worldly account of normative reasons according to which there is an ontological gap between these and the premises of practical thought, i.e. motivating considerations. While motivating considerations are individuated fine-grainedly, normative reasons should be classified as coarse-grained entities, e.g. as states of affairs, in order to explain certain necessary truths about them and to make sense of how we count and weigh them. As I briefly sketch, acting for normative reasons is nonetheless possible if the connection between normative reasons and motivating considerations is a competence-based correspondence.
Online veröffentlicht: 3. August 2015
Gesehen am 23.12.2025